2012
DOI: 10.1002/jssc.201100713
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of thermally stable nano‐structured self‐doped polythiophene coating for analysis of phthalate ester trace levels

Abstract: Nano-structured self-doped polythiophene (SPT) electrodeposited in the presence of fluorinated organic acid was applied as a thermally stable conductive polymer-based solid-phase microextraction (SPME) fiber candidate. Quantitative determination of trace levels of phthalate esters including dimethyl phthalate (DMP), diethyl phthalate (DEP), dibutyl phthalate (DBP), and diethylhexyl phthalate (DEHP) was carried out using this novel fiber, coupling with gas chromatography-flame ionization detector (GC-FID). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…When performing experiment with aqueous sample at temperatures of >90°C, the possibility of leaking small amount of water vapor into the needle rises. Expansion of water vapor would produce loss of analyte in the septum purge line and could affect the proper quantitation . Therefore, the higher temperatures >90°C were not tested for practical problems and the extraction temperature was set at 90°C in the subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…When performing experiment with aqueous sample at temperatures of >90°C, the possibility of leaking small amount of water vapor into the needle rises. Expansion of water vapor would produce loss of analyte in the septum purge line and could affect the proper quantitation . Therefore, the higher temperatures >90°C were not tested for practical problems and the extraction temperature was set at 90°C in the subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the preparation protocol, the fibers were reported with thicknesses ranging from dozens to hundreds micrometers and often possessed rather rough and granulated morphologies. To date, various analytes including organochlorine pesticides [191], phenols [192], phthalate esters [193], antibiotic drugs [194][195][196], and adrenolytic drugs [197], have been analyzed in different sample matrices, even in human plasma [195][196][197] and whole blood [194]. It is notable that Olszowy et al [196] have used several different poly(3-alkylthiophene)-coated SPME fibers to extract linezolid, which showed that the functional groups on the monomeric units could affect the EEs.…”
Section: Conductive Polymers and Modified Silicamentioning
confidence: 97%
“…Phthalates are primarily used as plasticizers in polymeric materials to increase their flexibility though weak secondary molecular interactions with polymer chains . Of the 18 commercial phthalate esters, the share of diethylhexyl phthalate (DEHP) is about 50% .…”
Section: Introductionmentioning
confidence: 99%
“…The Environmental Protection Agency (EPA) of the United States has regulated the admissible concentration level in drinking water of 6 μg/L for DEHP . The determination of phthalates usually involves capillary GC with flame ionization detection (FID) or MS, and HPLC with diode‐array and MS/MS detection, after sample preparations for enrichments, such as LLE , SPE , SPME , and so on.…”
Section: Introductionmentioning
confidence: 99%